Effect of Temperature and Time on Mechanical and Electrical Properties of HDPE/Glass Fiber Composites - Alkan, U.; Ozcanli, Y.; Alekberov, V. (KOREAN FIBER SOC, 2013)
In recent years, composites based on glass fiber reinforced polymer have been widely used in order to meet increasing durability and safety regulations, particularly in the power cable, automotive and plane industry. In this paper, mechanical and electrical properties of high density polyethylene (HDPE) and BDPE containing glass fiber polymer composites were investigated and compared at different temperatures. Composite materials were prepared with the hot pressing method. Tensile strength, % elongation and the modulus of elasticity (or Young's modulus) were determined for each sample at different temperatures. In addition to this, at different temperatures tau(sigma) and tau(E) have mechanical and electrical lifetime respectively, corresponding to mechanical tension (sigma) and electrical strength (E), and this was investigated for each sample. As compared to the mechanical and electrical properties of neat BDPE, HDPE/0.5 % glass fiber composites have been found to have better mechanical and electrical durability.
Keywords: Composites; Mechanical properties; Electric properties; Glass fiber; Strength; REINFORCED PLASTIC COMPOSITES; POLYETHYLENE COMPOSITES; DENSITY POLYETHYLENE; TENSILE DEFORMATION; POLYMER COMPOSITES; MORPHOLOGY; Materials Science; Polymer Science